2007
DOI: 10.1097/pec.0b013e31814efe06
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment and Management of Tinea Capitis in Children

Abstract: Tinea capitis is an infection of the scalp and hair shaft caused by dermatophyte fungi. It is seen in all age groups, and the incidence seems to be on the rise in North America. Clinical diagnosis of tinea capitis can be challenging, as symptoms can vary from minimal pruritus with no hair loss, to severe tenderness, purulence, and permanent scarring in inflammatory kerion lesions. The diagnosis of tinea capitis must be confirmed in the laboratory by using fungal stains or obtaining cultures, since treatment ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0
15

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 28 publications
1
27
0
15
Order By: Relevance
“…A study by Honig et al showed that although antibiotic and steroid therapy in addition to antifungals, help to reduce pruritus and scaling in patients with kerions, they did not reduce the time taken for kerions to flatten [13]. However, other reports that show that prednisolone used at 1 mg/kg/day for 7 days provides success [14,15]. Most dermatologists concur that steroids are useful in preventing the dreaded complication of scarring alopecia in inflammatory tinea capitis.…”
Section: Discussionmentioning
confidence: 98%
“…A study by Honig et al showed that although antibiotic and steroid therapy in addition to antifungals, help to reduce pruritus and scaling in patients with kerions, they did not reduce the time taken for kerions to flatten [13]. However, other reports that show that prednisolone used at 1 mg/kg/day for 7 days provides success [14,15]. Most dermatologists concur that steroids are useful in preventing the dreaded complication of scarring alopecia in inflammatory tinea capitis.…”
Section: Discussionmentioning
confidence: 98%
“…Etkilenen çocuklarda özgüven kaybı, değersizlik hissi gelişebilir 8 . Nadiren skar bırakan alopesi ve kerion olgularının beraberinde eritema nodosum görülebilir 15 .…”
Section: Klinikunclassified
“…Kültürde (%50) yalancı negatiflik görüldüğü hatırlanmalıdır 8 . Kültür için örnek nemlendirilmiş steril pamuk çubuk veya diş fırçasıyla alınabilir 6,15 .…”
Section: Tanıunclassified
See 1 more Smart Citation
“…Upon presentation, the patient was diagnosed with kerion, the most exaggerated cellular response to tinea capitis, a fungal infection of the scalp and hair shaft (1,2). A patient's history and physical examination results are often used to make a clinical diagnosis; however, clinical diagnosis is often unreliable, making laboratory confirmation necessary (3,4).…”
mentioning
confidence: 99%